2018
DOI: 10.1080/10225706.2018.1476256
|View full text |Cite
|
Sign up to set email alerts
|

China’s rapid urban ascent: an examination into the components of urban growth

Abstract: Having gone from 11.8% of its population inhabiting urban areas in 1950 to 49.2% by 2010, China represents the most dramatic urban transformation the world has seen. With the contemporary urban narrative presenting new challenges, particularly in terms of its unprecedented pace and scale, this paper conducts an inquiry into the nature and causes of China's rapid urban ascent. Making use of a new analytical framework, this paper maps out the changing stages of China's urban transition and examines the component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Notably, AD prevalence in Asian populations appears to be increasing, which may be related in part to rapid urbanization in many major metropolitan areas in Asia; for example, the population inhabiting China’s urban areas has increased from 11.8% in 1950 to 49.2% by 2010 [ 1 ]. The actual epidemiology of AD among different Asian populations remains unclear, but a growing body of evidence supports that this is an increasingly prevalent disease in many Asian countries with shifting demographics.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, AD prevalence in Asian populations appears to be increasing, which may be related in part to rapid urbanization in many major metropolitan areas in Asia; for example, the population inhabiting China’s urban areas has increased from 11.8% in 1950 to 49.2% by 2010 [ 1 ]. The actual epidemiology of AD among different Asian populations remains unclear, but a growing body of evidence supports that this is an increasingly prevalent disease in many Asian countries with shifting demographics.…”
Section: Introductionmentioning
confidence: 99%
“…The China Tourism Academy [1] reported that 30% of outbound tourists in China have switched from traditional mass tourism destinations to more nature-based destinations such as Sri Lanka, Sabah, and Bali. China's intensive urban development [4,5] and growth in urban populations [6], health-threatening pollution [7] and degrading environment [8] are common reasons why tourists visit nature-based areas instead of cities [1,9]. Nature reserves in China have also been extensively developing local nature-based tourism to accommodate the vast number of domestic tourists [10]; e.g., forest parks in China accommodated over 0.8 billion tourists in 2015 and made over 87 billion of tourism revenue [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that the number of persons who live outside of their countries of birth reached 281 million in 2020 globally, an increase from 108 million over the amount in 2000 (11). Although international migration does not have a direct impact on the world's population growth, and its impact on population growth is usually negligible in most countries compared to other demographic components, it has contributed significantly to the growth of populations in some countries.…”
Section: Growing Role Of International Migrationmentioning
confidence: 99%